Geochemical and energy storage properties of natural stones belong to limestone and Fe-shale families - Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In recent years, the rapidly increasing search for compact, sustainable, and low-cost energy storage systems has led researchers to seek natural materials with high energy storage capability. Taking motivation from this point, our study has been focused on examining the physical, chemical, and dielectric properties of Kayseri Limestone (LS-K), Yahyali stone (YS), and Edirne Limestone (LS-E) which have been collected from different regions of Turkey mines. The chemical content and structure of the stones have been determined by X-Ray Fluorescence analyzer and Fourier Transform Infrared spectrometry. The surface morphologies have also been visualized by Scanning Electron Microscope images. The frequency dependences of the components of complex permittivity, impedance, and ac conductivity have been examined at room temperature. It has been reported that LS-E has the ' greatest e value at 1-100 Hz interval. On the other hand, LS-K stands out as a low dielectric loss material with e '' values approximately 30 times and 24 times lower than YS and LS-E in the low-frequency range, respectively. Moreover, although the LS-K cannot have as high e ' values as the LS-E in the low-frequency region, it exhibits super-capacitive properties in a wide high-frequency interval of 47 kHz-40 MHz. The super-capacitive behavior of the LS-K has manifested itself with a phase angle of almost -90 degrees. In particular, the LS-K that has e '' values of 0.02 and less in the frequency interval of 0.1 MHz-40 MHz becomes an inexpensive and natural promising candidate for high-frequency energy storage applications.
Keywords: Natural stone; Limestone; Dielectric properties; Nyquist plot; Super-capacitive behavior; AC CONDUCTIVITY ANALYSIS; DIELECTRIC-RELAXATION; CARBONATE; IMPEDANCE; CONSTANT; BEHAVIOR; MODULUS; AREA; Geology; Meteorology & Atmospheric Sciences; Water Resources